Bandwidth Enhancement of a Microstrip-Line-Fed Printed Rotated Wide-Slot Antenna Based on Self-Shape Blending Algorithm - Aiting Wu; Furan Zhu; Pengquan Zhang; Zhonghai Zhang; Boran Guan (International Journal of Antennas and Propagation)
This paper proposes a self-shape blending algorithm to improve antenna bandwidth. A printed antenna is designed for bandwidth enhancement based on the proposed algorithm; this approach can also be used to enhance bandwidth in other applications. The antenna completely covers WLAN bands and WiMAX bands after the proposed algorithm is applied. The shape of the rotating slot and the parasitic patch also changes, which excites additional resonance and improves the impedance matching at high frequencies. Test results show that the proposed antenna can work from 2.07 GHz to 5.94 GHz with S11≤−10dB. Compared to a slot antenna without the self-shape blending algorithm, the bandwidth increases by more than 0.7 GHz.